Paliativna oskrba v intenzivni medicini - prikaz primera in pregled literature - Ećimović, Patricija (Zdravniški vestnik, 2009)
Background Population of patients who are being treated in intensive care units in developed world is becoming older and with more serious comorbidities, resulting in rising numbers of patients with unfavourable prognosis. As continuation of intensive care becomes less efficient in these patients, the alternative they have to be offered is good quality palliative care. Management of such patients is complex, multidisciplinary and currently still inadequate, mainly because health care providers in intensive care are still unfamiliar with concept of palliative care and more importantly because palliative care seems to be contradictory to saving life at all cost, as we doin intensive care medicine. Conclusions We would like to present a review ofcurrent literature on palliative care in intensive medicine.
Keywords: Aged; Comorbidity; Critical Illness; Duodenal Ulcer; Duodenalni ulkus; Intensive Care Units; intenzivna medicina; Intenzivna oskrba, enote; Kritična bolezen; Neoplasms; Novotvorbe; Paliativna oskrba; Palliative Care; Peptic Ulcer Perforation; Peptični ulkus, perforacija; prognoza; Soobolevnost; Starostniki; Surgery; tumor